2020
DOI: 10.1093/ofid/ofaa071
|View full text |Cite
|
Sign up to set email alerts
|

Early Experience With Eravacycline for Complicated Infections

Abstract: Eravacycline (ERV) was used in 35 patients for various infections. The most common pathogen was Klebsiella pneumoniae, and 30-day survival was 74%. Absence of 30-day recurrence and resolution of signs and symptoms of infection were 91% and 57%, respectively. ERV was well-tolerated, with adverse events leading to drug discontinuation in one patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
2
30
0
Order By: Relevance
“…and VRE. Of note, in the Alosaimy et al study [ 23 ], four patients had polymicrobial infections, and CRE was present in all studies.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…and VRE. Of note, in the Alosaimy et al study [ 23 ], four patients had polymicrobial infections, and CRE was present in all studies.…”
Section: Discussionmentioning
confidence: 95%
“…There have been three previously reported real-world clinical experience studies involving eravacycline [ 20 – 23 ], the largest of which reported on 35 patients. These studies include hospital and OPAT settings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations